GAMIFICATION IN VIRTUAL ECOLOGY (GIVE): ENHANCING CLASSROOM ENGAGEMENT IN PHYSICAL EDUCATION - M. Marcaida, John Louise (LP2M Universitas Bina Mandiri Gorontalo, 2023)
The study was geared towards determining the influence of integrating Gamification in a Virtual Ecology (GIVE) in enhancing the classroom engagement in physical education among Senior High School students at a state university in Pampanga, Philippines. This qualitative-descriptive study included a complete enumeration of the Grade 12 Technical-Vocational- Livelihood (TVL) students who voluntarily participated in this qualitative investigation (n = 58) by responding to an open-ended questionnaire. Results of the open-ended questionnaire decipher the influence of gamification on student’s level of engagement and the barriers encountered upon its inclusion. The study utilized Braun and Clarke's Thematic Analysis strategy, which was aided by a computer-assisted qualitative analysis, MAXQDA Analytics Pro 2022. The study revealed two emerging themes that described the influence of gamification in the students' virtual ecology, namely: (1) the effects of the integration of gamified instruction on students’ engagement; and (2) students' problems in using gamified instruction. Findings of this study may predate the institutionalization of the prospective enhancement of the teacher’s capabilities through the aid of gamification to improve the classroom engagement of the students in a virtual ecology towards a better understanding of the lesson in physical education settings.